2014
DOI: 10.1111/ene.12582
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐related symptoms and sleep‐disordered breathing in adult Pompe disease

Abstract: In adult Pompe disease, sleep disturbances are a common cause of excessive daytime sleepiness and fatigue. Sleep-related symptoms may be indicative of respiratory muscle weakness and should give rise to further work-up of sleep-disordered breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 27 publications
1
58
0
3
Order By: Relevance
“…Mellies et al were the first to explore sleep-disordered breathing in late onset Pompe disease, showing the increased prevalence of obstructive sleep apnea (OSA) and hypoventilation in this group. Late-onset Pompe patients have a high prevalence of poor sleep quality, fatigue, sleepiness, sleep apnea, and hypoventilation [Mellies et al, 2001;Boentert et al, 2014]. Similarly, we reported a high prevalence of sleep-disordered breathing amongst patients with infantile-onset Pompe disease [Kansagra et al, 2013].…”
Section: Introductionsupporting
confidence: 66%
“…Mellies et al were the first to explore sleep-disordered breathing in late onset Pompe disease, showing the increased prevalence of obstructive sleep apnea (OSA) and hypoventilation in this group. Late-onset Pompe patients have a high prevalence of poor sleep quality, fatigue, sleepiness, sleep apnea, and hypoventilation [Mellies et al, 2001;Boentert et al, 2014]. Similarly, we reported a high prevalence of sleep-disordered breathing amongst patients with infantile-onset Pompe disease [Kansagra et al, 2013].…”
Section: Introductionsupporting
confidence: 66%
“…Dyspnea, which results in an increased sense of effort, is a subjective sensation of breathing discomfort, likened to being smothered or suffocated. Nocturnal hypoventilation disrupts normal sleep architecture, initially in REM sleep leading to excessive daytime fatigue and morning headaches due to hypercapnia [11, 12]. Other symptoms of nocturnal hypoventilation, include insomnia, hypersomnolence, or impaired cognition.…”
Section: Introductionmentioning
confidence: 99%
“…In LOPD, symptoms of respiratory muscle weakness are common and correlate with self-reported sleep quality, fatigue, and impaired daytime performance. 3 Our study underlines that the presence of SDB may be associated with increased fatigue and significantly reduces HRQoL in both physical and mental aspects.…”
Section: Discussionmentioning
confidence: 57%
“…It seems surprising that the SF-36 PCS score appeared to decrease again between timepoints T2 and T6. However, we previously showed that physical HRQoL is more reduced in patients using NIV than in patients without home ventilatory support, 3 which may be attributed to various aspects such as older age, more rapid functional deterioration with more advanced disease, and the use of long-term positive pressure ventilation itself.…”
Section: Discussionmentioning
confidence: 96%